Empirical evaluation of crystalline silicon and amorphous silicon thin-film photovoltaic module performance using current-voltage characteristics - Sumalde, Adrian Augusto M.
The behavior of solar photovoltaic (PV) modules has been the subject of many previous studies, with evaluation coming from both a simulation perspective and a field-based research perspective. This study evaluated the response of monocrystalline silicon, polycrystalline silicon, and amorphous silicon (a-Si) thin-film solar photovoltaic (PV) modules with respect to four simultaneous environmental parameters, namely: irridance, ambient temperature, front panel temperature, and back panel temperature. For each module type, its current-voltage (I-V) characteristics were determined and fitted a two-term exponential model, then used to calculate the following electrical parameters: open-circuit voltage, short-circuit current, maximum power and its associated current and voltage, fill factor, and efficiency. The data was subjected to the following tests: Analysis of variance (ANOVA), determination of Pearson's correlation coefficient, and multiple linear regression coupled with factor analysis. The results of this study include the rankings of the influence of each environmental parameter for each PV module type, as well as the statistically significant models developed for short-circuit current, maximum power, and maximum power current. Finally, the effective cost per watt was estimated for each module, considering the projected maximum power, the cost of each module, and the land cost per square meter.